Big Health and Micro-environment from the Perspective of Daily Life - Yu CHENG; Jiaye LI; Liping HE; Jingsheng CHEN (Yixue yu zhexue, 2025)
The relationship between individual health micro-environments and the broader concept of big health can be metaphorically compared to the Buddhist concept of a mustard seed containing mount sumeru: seemingly small yet encompassing vastness, illustrating their interdependent and mutually reinforcing nature. The concept of big health integrates three interconnected dimensions: individual health, societal health, and environmental health, emphasizing the importance of comprehensive well-being maintenance and promotion. However, health practices in daily life are not merely technical acts, but also serve as carriers of cultural meaning. Anthropology, through its study on daily life practices and the methodology of ethnography, provides a new perspective to understand health by focusing on the individual's daily health activities. It reveals the multiple logics individuals adopt when encountering health-related challenges, thereby offering practical pathways to enhance the overall health of society and advance the implementation of the Healthy China Initiative.